Study of Recommendations For The Best Candidates in a Decision Support System Using Fuzzy Multicriteria Based on Simple Additive Weighting - Sinar Sinurat (Jurnal Info Sains : Informatika dan Sains, 2023)
Recommendations for prospective workers are determined based on the fulfillment of the criteria tested by participants, whereas fuzzy multicriteria based on Simple Additive Weighting are used to process available data to produce participant assessment information that has the potential to be accepted. The multi-criteria-based system shows the accuracy of candidate recommendations according to ranking. The fuzzy set will show the paradigm of handling uncertainty and ambiguity in the behavior of determining candidates effectively and choosing based on Fuzzy Multi-Criteria Decision Making (FMCDM) in the candidate labor market. The argument for selecting the title is adjusted to the Fuzzy Multicriteria decision-making pattern. Improving the quality of determining the workforce that is known by the public in order to train job seekers in both technical and managerial training so that reliable prospective workers are obtained who can compete in the world of work This method is aimed at reducing the large number of unemployed people who continue to grow, so placement of local workers is usually carried out either through the formal or non-formal sectors in order to create new prospective entrepreneurs or even look for opportunities between jobs.